Monitoring River Water Levels to Complete Flood using Ultrasonic Sensors - Nur Khafidhoh; Ardy Ansyah (NEWTON: Networking and Information Technology, 2022)
Most rivers in flood-prone areas often use manual methods to find out how much water is in the river by looking directly at the water surface, therefore sluice guards must be alert every time to avoid overflowing water in the river. The sluice gate is controlled by the officer in charge of keeping the water in the river stable, not less or not exceeding the specified limit. With this background, the tool is designed to monitor the water level in the river connected to the river using ultrasonic sensors which are processed using a microcontroller and a wifi network as a means of internet connection and monitoring media for the blynk platform interface. Which will continue to provide information and warnings to the operator if the water level reaches the normal limit through a warning on the blynk platform and will turn on the buzzer as a warning to the operator or user, so that with a tool designed in this study the water level can be known automatically. This tool can be made as an early warning of potential flood hazards in river areas. In other words, there will be effectiveness in the application of appropriate technology